Stress Degradation Studies and HPLC Method Development for Simultaneous Estimation of Prednisolone Acetate and Chloramphenicol in Topical Eye Drops - Ahsan Hafiz, M.; Idrees, Muhammad; Tariq, Imran; Amjad, Sohail; Ali Shah, Arshad (Asian Journal of Chemistry, 2014)
A rapid reversed phase liquid chromatographic method was developed and validated for simultaneous HPLC determination of chloramphenicol and prednisolone acetate. The proposed method was effectively applied on separation of chloramphenicol and prednisolone acetate in the presence of excipients and degradation products in eye drops. Chromatographic separation was achieved using combination of ammonium acetate buffer (0.02 M; pH 4) and methanol (30:70 v/v) at a flow rate of 1.5 mL/min. The effluent from column was monitored at 276 and 245 nm for chloramphenicol and prednisolone acetate, respectively. A good linear relationship was observed over the concentration ranges 0.0256-80 and 0.064-200 μg/mL with correlation coefficient 0.9999 and 0.9999 for chloramphenicol and prednisolone acetate, respectively. Calculated LOQ were 36 ng/mL for chloramphenicol and 31 ng/mL for prednisolone acetate. Active ingredients (chloramphenicol and prednisolone acetate) and degradation products were resolved in less than 4 min. The developed method was validated according to ICH guidelines.